Web-Based Application Development for Circulation Services: Integrating Digital Receipt and Reminder Message Features - Putri Ridha Karima; Prasetyawan Adi; Suhidan Shamila Mohamed (Department Library of Governance Institut of Home Affairs, 2025)
Abstract Background: Delays in book returns, manual management practices, and limited access to borrowing information, along with suboptimal communication strategies, have reduced the quality of circulation services and hindered the optimal use of library collections. Based on these issues, developing a web-based circulation system equipped with digital receipt delivery and automated reminder messages is considered essential to improve service performance and ensure better utilization of library resources. Purpose: This study aims to develop a system that delivers digital receipts and automated reminder messages to help reduce delays in book returns. Method: This research employed a Research and Development (R&D) method using the ADDIE model (analysis, design, development, implementation, and evaluation). The study applied descriptive quantitative analysis with Likert scales and validation percentages, complemented by qualitative analysis from expert and respondent feedback. Result: The validation results indicated scores of 91% from material experts, 90% from media experts, and 96% from field trials, classifying the application as highly valid and feasible for use. The media evaluation also demonstrated that the application performs effectively, is user-friendly, and contributes to the enhancement of library service quality. Conclusion: The development of a web-based circulation service application using the ADDIE model has resulted in a system integrated with digital receipt and automated reminder features. These features assist users in managing their borrowing activities more efficiently and punctually. Validation results from experts and field trials confirmed that the application is highly valid, user-friendly, and feasible for implementation in school library services.